2020
DOI: 10.1039/d0sc03429k
|View full text |Cite
|
Sign up to set email alerts
|

Heavy chalcogenide-transition metal clusters as coordination polymer nodes

Abstract: Recent developments, challenges, and opportunities in using polynuclear transition metal heavy chalcogenide clusters as nodes for coordination polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 215 publications
0
30
0
Order By: Relevance
“…A special class of cluster-based aggregation combines the structural features and functionalities of both polynuclear coordination clusters and metal-organic frameworks (MOFs), two fascinating families of crystalline molecular materials. [1][2][3][4][5][6][7][8][9][10] This type of aggregation has attracted much attention in recent years because of its intriguing potential applications in gas absorption, [11][12][13][14] photoluminescence, 15,16 catalysis, 17,18 and magnetic materials. [19][20][21] Extensive studies have been conducted on cluster-based coordination polymers (CPs) with diverse dimensions, topologies, shapes, and functional expansions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A special class of cluster-based aggregation combines the structural features and functionalities of both polynuclear coordination clusters and metal-organic frameworks (MOFs), two fascinating families of crystalline molecular materials. [1][2][3][4][5][6][7][8][9][10] This type of aggregation has attracted much attention in recent years because of its intriguing potential applications in gas absorption, [11][12][13][14] photoluminescence, 15,16 catalysis, 17,18 and magnetic materials. [19][20][21] Extensive studies have been conducted on cluster-based coordination polymers (CPs) with diverse dimensions, topologies, shapes, and functional expansions.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a bis-triazole ligand, 5,5′-di( pyridin-2-yl)-3,3′-bi(1,2,4-triazole) (H 2 dpbt), was selected to construct a discrete {Fe 5 .5MeOH} n ({Fe 5 }-2D) (MEK = methylethyl ketone) could be isolated. It was also evaluated whether an increase in the reaction temperature could drive the dimension augmentation.…”
Section: Introductionmentioning
confidence: 99%
“…The key attributes of CuSCN are its optical transparency and hole-transporting ability (p-type conductivity), resulting from the electronic structure comprising mainly Cu I 3d 10 states hybridized with S 3p at the valence band maximum (VBM) and high-energy SCN – π* states at the conduction band minimum (CBM). , Compared to oxygen-bonded ligands, the improved energy matching between metal and sulfur atoms can provide efficient charge transport pathway in coordination polymers (CPs); indeed the structure of CuSCN can be visualized as 2D Cu–S sheets connected via CN bridges. Furthermore, we recently showed that tin­(II) thiocyanate [Sn­(SCN) 2 ] is another transparent CP-based semiconductor with the VBM dominated by S 3p and N 2p states with contributions from Sn II 5s 2 lone pair electrons and can be used as an ultrathin anode interlayer in OPVs. , Sn­(SCN) 2 was also employed as a dopant in an electron transport layer that led to significant enhancements in OPV and PSC efficiencies .…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] The key attributes of CuSCN are its optical transparency and hole-transporting ability (p-type conductivity), resulting from the electronic structure comprising mainly Cu I 3d 10 states hybridized with S 3p at the valence band maximum (VBM) and high-energy SCN − π* states at the conduction band minimum (CBM). 24,25 Compared to oxygen-bonded ligands, the improved energy matching between metal and sulfur atoms can provide efficient charge transport pathway in coordination polymers (CPs); [26][27][28] indeed the structure of CuSCN can be visualized as 2D Cu-S sheets connected via CN bridges. Furthermore, we recently showed that tin(II) thiocyanate [Sn(SCN) 2 ] is another transparent CP-based semiconductor with the VBM dominated by S 3p and N 2p states with contributions from Sn II 5s 2 lone pair electrons and can be used as an ultrathin anode interlayer in OPVs.…”
Section: Introductionmentioning
confidence: 99%